Early versus late drainage of pancreatic necrotic fluid collections: a systematic review and meta-analysis - Shivanand Bomman; Andrew Canakis; Muaaz Masood; Jagpal S. Klair; Rodrigo Alvarez; Arunkumar Muthusamy; Shruti Chandra; Avin Aggarwal; Hemanth Gavini; Rajesh Krishnamoorthi (2025)
Necrotizing pancreatitis can be complicated by necrotic fluid collections (NFCs). International guidelines recommend waiting 4 weeks for the collection to mature before interventional management. With the advances in endoscopic drainage, the need to delay drainage by 4 weeks is unclear. We aimed to compare early drainage (ED: <4 weeks) vs. late drainage (LD: ≥4 weeks) of NFCs. Literature searches through multiple databases were performed to identify studies that investigated outcomes of ED vs. LD of NFCs. Our primary outcome was the complication rate among these groups. The secondary outcomes included the number of patients requiring subsequent necrosectomies, and mortality. We identified 9 studies with 855 patients (320 ED and 535 LD). The complication rates (rate ratio 1.060, 95% confidence interval [CI] 0.79-1.42; P=0.69; I 2=51.61) and the number of patients requiring subsequent necrosectomies (odds ratio [OR] 2.15, 95% CI 0.86-5.35; P=0.099; I 2=79.81) were similar in both groups. Mortality was slightly higher in the ED group (OR 1.94, 95%CI 1.05-3.59; P=0.033; I 2=0). Our study suggests that ED can be performed if needed in carefully selected patients without an increase in complications or subsequent necrosectomies. However, mortality was slightly higher compared to LD. A multidisciplinary team approach is necessary for considering ED.